Development of polymer-assisted nanoparticles and nanogels for cancer therapy: An update - Bibi Noorheen, H. M. N.; Ooi, L. T.; Shameli, Kamyar; Nuraina, A. D.; Jahid, M. M. I.; Pushpamalar, Janarthanan; Teow, Sin Yeang * (MDPI, 2021)
With cancer remaining as one of the main causes of deaths worldwide, many studies are undergoing the effort to look for a novel and potent anticancer drug. Nanoparticles (NPs) are one of the rising fields in research for anticancer drug development. One of the key advantages of using NPs for cancer therapy is its high flexibility for modification, hence additional properties can be added to the NPs in order to improve its anticancer action. Polymer has attracted considerable attention to be used as a material to enhance the bioactivity of the NPs. Nanogels, which are NPs cross-linked with hydrophilic polymer network have also exhibited benefits in anticancer application. The characteristics of these nanomaterials include non-toxic, environment-friendly, and variable physiochemical properties. Some other unique properties of polymers are also attributed by diverse methods of polymer synthesis. This then contributes to the unique properties of the nanodrugs. This review article provides an in-depth update on the development of polymer-assisted NPs and nanogels for cancer therapy. Topics such as the synthesis, usage, and properties of the nanomaterials are discussed along with their mechanisms and functions in anticancer application. The advantages and limitations are also discussed in this article.